Extracurricular classes on the study of historical and cultural monuments of England - Pirmanova, Gavkhar Nazarkulovna; Yarkulovna, Saidova Surayyo; Najmiddinovna, Khudoyarova Dildora; Mustafakulovich, Isayev Anvar; Shavkatovna, Jurayeva Nargiza (Linguistics and Culture Review, 2021)
Successful training depends not only on active vocabulary but mainly on the presentation of cultural material about England. First of all - from the general information about the greatest ancient-architecture as a whole which can be successfully solved during non-school time. With the maximum use of intellectual and creative abilities of adolescence, including adequate communication and education activities of adolescents. The article reveals the contents of new technologies, non-traditional and original, innovative methods, modern information tools that are effectively used in extracurricular activities, primarily for the development of intellectual and creative activities of teenagers - precisely not included in the teaching scope - on potentially-effective material about monuments of history and culture (Great Britain, England).